2022
DOI: 10.3389/fonc.2022.968360
|View full text |Cite
|
Sign up to set email alerts
|

4-1BB: A promising target for cancer immunotherapy

Abstract: Immunotherapy, powered by its relative efficacy and safety, has become a prominent therapeutic strategy utilized in the treatment of a wide range of diseases, including cancer. Within this class of therapeutics, there is a variety of drug types such as immune checkpoint blockade therapies, vaccines, and T cell transfer therapies that serve the purpose of harnessing the body’s immune system to combat disease. Of these different types, immune checkpoint blockades that target coinhibitory receptors, which dampen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 106 publications
1
14
0
Order By: Relevance
“…Few studies have examined the amounts of the protein 4-1BB in various cancer cells such as lung, pancreas, etc. [11][12][13] Our study found increased expression of 4-1BB in PBMCs from OC and OPC compared to HC (►Fig. 1A).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Few studies have examined the amounts of the protein 4-1BB in various cancer cells such as lung, pancreas, etc. [11][12][13] Our study found increased expression of 4-1BB in PBMCs from OC and OPC compared to HC (►Fig. 1A).…”
Section: Discussionmentioning
confidence: 58%
“…Consequently, combining multiple medications, such as PD-1 with 4-1BB, or Programmed death-ligand 1 (PD-L1) with 4-1BB, to improve the safety and efficacy of cancer therapies is an alternative novel cancer immunotherapy strategy. 4,13,29…”
Section: Discussionmentioning
confidence: 99%
“…63 Agonistic antibodies targeting co-stimulatory receptors such as 4-1BB may again yield different results. 64 Notably, unlike anti-PD1-directed agents, the 4-1BB agonist urelumab was found to have dose-limiting toxicities. 65 In contrast, the 4-1BB agonistic antibody utomilumab was found not to have dose-limiting toxicities in the range tested.…”
Section: Discussionmentioning
confidence: 99%
“…Meant to act as guards against excessive immune response, they can also act as avenues for tumor cells to escape immunosurveillance. , A few well-known examples of inhibitory immune checkpoint molecules include programmed cell death protein-1 (PD-1), cytotoxic T lymphocyte-associated antigen-4 (CTLA-4; also known as B7, CD152), B and T lymphocyte attenuator (BTLA; also known as CD272), and lymphocyte-activation gene 3 (LAG-3; also known as CD223) , among others. For the stimulatory pathways, glycoproteins such as OX40 receptors (also known as CD134 and TNFRSF4) , and 4–1BB (also known as CD137) are few well-known examples of immune checkpoint molecules. Expressed on cell surface, immune checkpoint molecules modulate the activity of T cells and it is this feature that can be exploited to our advantage.…”
Section: Adc-based Combination Therapiesmentioning
confidence: 99%